The Quality Of Nastar Produced From The Substitution Of Taro Flour - Fitriani, Nurjannah; Holinesti, Rahmi (Universitas Negeri Padang, 2022)
This study aims to analyze the quality of nastar resulting from the substitution of taro flour as much as 15%, 30%, and 45% which includes shape, color, aroma, texture, and taste. This type of research is a true experiment using the Completely Randomized Design (CRD) method and carried out with 4 treatments and 3 repetitions. This research was conducted in August – September 2021 at the Catering Workshop, Department of Family Welfare, Faculty of Tourism and Hospitality, Padang State University. The object of this research is nastar by replacing wheat flour with taro flour as much as 15%, 30%, and 45% of the quality of nastar. The types and sources of data used are primary data obtained directly from 5 expert panelists by filling out the organoleptic test format on the quality of taro flour nastar. Data analysis used Analysis of Variance (ANOVA). If there is a significant effect, the Duncan test will be carried out. The results showed that the substitution of taro flour had no significant effect on the quality of the shape, aroma, texture, and taste of taro flour nastar. While a significant effect is on the quality of color and taro itching on taro flour nastar. The result of the best quality test of taro flour nastar is the treatment (X1) with 15% taro flour substitution. For further research, it is recommended to conduct further research on nutritional content or shelf life with the best substitution of taro flour as much as 15% (X1)